Fault displacement analysis using a multidisciplinary approach on the Gerede Segment of the North Anatolian Fault Zone. Issue 164 (January 2023) - Gunaydin, Osman; Inceyol, Yasar; Cetin, Hasan; Ulukavak, Mustafa
Abstract: The North Anatolian Fault Zone (NAFZ) is the world's most seismically significant strike-slip fault and Turkey's most active tectonic structure. A segment of NAFZ known as Gerede is located in northwest Turkey. It is debatable whether the Gerede segment of the NAFZ exhibits evidence of tectonic creep formation. The movement of the Gerede Segment of the NAFZ was investigated using various methods in this study. The Global Navigation Satellite System (GNSS) and soil mechanics-based methods were used in the Gerede Segment of the NAFZ for fault displacement analysis using a multidisciplinary approach. The GNSS technique is widely used in geodynamics-kinematics and cartography studies of earth crust movements, as well as in determining deformations during earthquake periods and as a source of data in defining geological and atmospheric phases. By establishing a GNSS network composed of regional or geodetic station points around the fault zone, it is possible to determine the deformations, velocities, and possible seismic slip rates of permanent GNSS stations on this network. The shear box test is used in soil mechanics to determine the shear strength parameters c and φ. A shear box test is performed to determine the pattern of fault movement (seismic or aseismic) and to determine the shear strength parameters (c, φ). An undisturbed block sample from a paleoseismology trench was used for a consolidated drained (CD) type shear box test. It was found that the fault movement near the Gerede Segment was not creeping. This study makes a new contribution to the debate on whether the Gerede Segment's movement pattern is creep or seismic. Highlights: Paleoseismology uses geodetic and soil mechanics to determine shear stress parameters to find fault movement patterns. Determination of deformations by geodetic methods on the North Anatolian Fault Zone. Considering velocities with CORS-TR GNSS stations' observations around the NAFZ.